Thin Capitalization, Transfer Pricing Aggresiveness, Penghindaran Pajak - Teza Deasvery Falbo; Amrie Firmansyah (Universitas Agung Podomoro, 2018)
The increase in tax revenue in Indonesia is not accompanied by an increase in tax ratio The low tax ratio indicatestax avoidance practices in Indonesia. Some tax avoidance practices can be conductedthrough transfer pricing and thin capitalization.This study is aimed to examine empirically the effect of thin capitalization as well as transfer pricing aggressiveness on tax avoidance practice in Indonesia. This study uses manufacturing companies which are listed on Indonesia Stock Exchange (IDX) within the period 2013-2015. Using purposive sampling, the selected samples in this study are 90 companies, so the total sample is 270 samples. The hypothesis examination used in this study is multiple linear regression analysis of panel data.The results of this study suggest that thin capitalization is positively associated with tax avoidance,while transfer pricing aggressivenessis not associated with tax avoidance.